Does lower lifetime fluoridation exposure explain why people outside capital cities have poor clinical oral health?. (26th February 2016) - Crocombe, LA; Brennan, DS; Slade, GD
Abstract: Background: Australians outside state capital cities have greater caries experience than their counterparts in capital cities. We hypothesized that differing water fluoridation exposure was associated with this disparity. Methods: Data were the 2004–06 Australian National Survey of Adult Oral Health. Examiners measured participant decayed, missing and filled teeth and DMFT Index, and lifetime fluoridation exposure was quantified. Multivariable linear regression models estimated differences in caries experience between capital city residents and others, with and without adjustment for fluoridation exposure. Results: There was greater mean lifetime fluoridation exposure in state capital cities (59.1%, 95% confidence interval = 56.9, 61.4) than outside capital cities (42.3, confidence interval = 36.9, 47.6). People located outside capital city areas had differing sociodemographic characteristics and dental visiting patterns, and a higher mean DMFT (capital cities = 12.9, non‐capital cities = 14.3, p = 0.02), than people from capital cities. After adjustment for sociodemographic characteristics and dental visits, DMFT of people living in capital cities was less than non‐capital city residents (regression coefficient = 0.8, p = 0.01). The disparity was no longer statistically significant (regression coefficient = 0.6, p = 0.09) after additional adjustment for fluoridation exposure.